2021
DOI: 10.26633/rpsp.2021.118
|View full text |Cite
|
Sign up to set email alerts
|

Advancing environmental public health in Latin America and the Caribbean

Abstract: This paper highlights the important leadership role of the public health sector, working with other governmental sectors and nongovernmental entities, to advance environmental public health in Latin America and the Caribbean toward the achievement of 2030 Sustainable Development Goal 3: Health and Well-Being. The most pressing current and future environmental public health threats are discussed, followed by a brief review of major historical and current international and regional efforts to address these conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…Starting with an overview of the American continent and especially Latin America and the Caribbean countries, Korc and Hauchman ( 2021 ) made an important warning about the large number of people in several countries, such as the Dominican Republic, Paraguay, Venezuela, Haiti, and Belize, that do not have clean primary sources to cook in their homes, needing to resort to the use of wood and charcoal and producing high levels of pollution, in the middle of 2018. These authors also showed that among the 35 American countries studied, only Canada and the USA had no annual records of PM 2.5 concentration above WHO recommendations in 2016, a very worrying scenario.…”
Section: Air Pollutionmentioning
confidence: 99%
“…Starting with an overview of the American continent and especially Latin America and the Caribbean countries, Korc and Hauchman ( 2021 ) made an important warning about the large number of people in several countries, such as the Dominican Republic, Paraguay, Venezuela, Haiti, and Belize, that do not have clean primary sources to cook in their homes, needing to resort to the use of wood and charcoal and producing high levels of pollution, in the middle of 2018. These authors also showed that among the 35 American countries studied, only Canada and the USA had no annual records of PM 2.5 concentration above WHO recommendations in 2016, a very worrying scenario.…”
Section: Air Pollutionmentioning
confidence: 99%
“…Addressing environmental infrastructure gaps is crucial for enhancing ECD in Latin America and the Caribbean (LAC) region (Günther and Lahoti, 2021;Schady, 2015;Korc and Hauchman, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…El planeta se enfrenta a una triple emergencia medioambiental ligada al cambio climático, la contaminación y cambios en la biodiversidad, las cuales, según el último informe presentado por la ONU, (2021) suponen una seria amenaza para la humanidad, causando casi 9 millones de muertes prematuras por año, una cifra que duplica los fallecimientos a causa del Sars-Cov-2 en el mismo lapso, triplica la letalidad provocadas por enfermedades tales como sida, malaria y tuberculosis; y a su vez, multiplica por 15 las muertes ocasionadas por las guerras, los asesinatos y otras formas de violencia (Korc & Hauchman, 2021;ONU, 2021).…”
Section: Introductionunclassified